Management of Conjoined Twins in Kano, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Introduction:Conjoined twins are abnormalities of twinning in which two individuals are incompletely separated. Conjoined twins can be symmetric or asymmetric and continue to raise significant ethical and legal arguments, resulting in much pressure on the managing teams and hospitals.Patients and Methods:We report 4 cases of conjoined twins, an ischiophagus dipus, pygophagus, thoracoomphalophagus tetrapus, and a parasitic twin tripus. All cases had no prenatal diagnosis and were delivered via spontaneous vaginal delivery. The pygophagus tetrapus was separated and a mortality of 50% was recorded in the immediate post separation period; the surviving twin is 8 years old and doing well. Two were lost due to severe birth trauma, and the last was lost to overwhelming from an infected gluteal congenital defect.Results and Discussion:Conjoined twins are one of the most fascinating congenital malformations not only to the medical practitioners but to communities and general public also. To our knowledge, as of 2012, only 15 cases have been reported from Nigeria. The incidence is 1:50,000–1:100,000 births. Females are affected more frequently than males by a ratio of 3:1. Separation of conjoined twins is a complicated procedure. The importance of a multidisciplinary team approach with several rehearsals of all aspects (surgical, anesthetic intensive care, transfer from the theatre to intensive care unit, and nursing) of the operative procedure cannot be overemphasized.Conclusion:Conjoined twins are one of the most fascinating congenital malformations. Early prenatal diagnosis, antenatal care, choice of mode of delivery, thorough assessment of the extent of shared organs to guide decisions on surgical separation, adequate planning, and rehearsals can reduce morbidity and mortality in these patients. In our series, all pregnancies and deliveries were unsupervised leading to poor outcome.